Effect of Type 2 Diabetes Mellitus on Extracellular Superoxide Dismutase: Without Complications among Iraqi Patients - Haddad, Namir I.; Nori, Essam; Ali, Sana'a H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The current study includes (130) T2DM patients (group P) [51 males and 79 females with an ages range (35 to 55) and ages mean 49.89 years], they are sub-grouped into three categories according to their HbA1c value. patients with HbA1c less than 7 are considered as good controlled diabetic patients (30 patients) (group P1), while patients with HbA1c between 7 and 8 are considered as medium controlled diabetic patients (40 patients) (group P2), and the patient whom their HbA1c more than 8 are considered as uncontrolled diabetic patients (50 patients) (group P3). The patients group results are compared to control healthy subjects (35 subjects) (group C) [14 males and 21 Females with age range 45.51 years] matched for age, gender and BMI were included in the study. Patients and controls groups were characterized in terms of age (year), duration of DM (year), body mass index (BMI) (Kg/ m2) , serum insulin (Î¼IU/ml) , fasting serum glucose (FSG) (mg/dl), Homeostatic model assessment (HOMA) parameters using HOMA2 calculator, MDA (mmol/L) using TBA reaction method, \and EC-SOD activity (U/ml) , using riboflavin/NBT method. were measured for patients and control subjects. The HbA1c, FSG, FSI and I.R have been found to be significantly higher in diabetic patients group (P) in comparison to group C. The HOMA parameters (S% and Î²%) have been found to be significantly higher in group C as compared to diabetic patients group (group P), serum specific SOD activity, EC-SOD activity found to be significantly higher in control group C in comparison to patients group P. Serum MDA level showed a significantly higher value in diabetic patients group P in comparison to control group C. The FSG, FSI and I.R have been showed that they are increased as HbA1c increase, i.e. these parameter were higher in group P3 compared with group P2, group P1 and group C. HOMA parameters (S% and Î²%) have shown a significant decrease as HbA1c increase, i.e. these parameter were lesser in group P3 than group P2, and were higher in group P2 than group p1, although these parameters were lower in patients group P than control group C. and serum EC-SOD activity were decreased as HbA1c increase, i.e. SOD activity, specific SOD activity and serum EC-SOD activity were found to be significantly higher in group P1 comparing with group P2 and P3, while serum MDA level in group P3 was significantly higher than group P2, and P1. The serum MDA level in group P1 and group P2 showed a significant positive correlation with age. In group P3, MDA showed a significant negative correlation with serum Cr level, while, a significant positive correlation was observed with age, duration of DM, and HbA1c.We can conclude that the T2DM patients have a risk of oxidative stress due to increasing the level of serum MDA and decreasing EC-SOD activity. The HbA1c value between 7 to 8 % can not be considered as an acceptable HbA1c value, due the severing of oxidative stress rising manifested clearly in this patients group.